AN ANALYSIS OF SUBTITLING STRATEGIES IN CLASH-A-RAMA ANIMATION SEASON 1 EPISODE 1, 2 AND 8 - Dohan Zuhudiyanto; Dewi Wulan Sari (Asosiasi Dosen Muda Indonesia, 2024)
Subtitling strategies is technique that can help the translators to do their job in translating subtitle in the movie. The problem of this research is what subtitling strategies are used in Clash-A-Rama animation season 1 Episode 1,2 and 8? The aim of this research is to find out subtitling strategies used in Clash-A-Rama Animation Season 1 Episode 1, 2 and 8. In order to conduct the research, the researcher used qualitative research method. The researcher used 379 utterances from Clash-A-Rama Animation Season 1 Episode 1, 2 and 8 as the data. The result of the research showed that some of the utterances used more than one subtitling strategy and all of subtitling strategies are found in this research. They are paraphrase (230 data), transfer (122 data), condensation (32 data), imitation (14 data), deletion (14 data), expansion (9 data), dislocation (2 data) resignation (2 data), decimation (1 data) and transcription (1 data).